Examining the Importance of the Teachers' Emotional Support for Students' Social Inclusion Using the One-with-Many Design - Hogekamp, Zarina; Blomster, Johanna K.; Bursalıoğlu, Aslı; Călin, Mihaela C.; Çetinçelik, Melis; Haastrup, Lauge; van den Berg, Yvonne H. M. (Frontiers in Psychology, 2016)
The importance of high quality teacher-student relationships for students’ well-being has been long documented. Nonetheless, most studies focus either on teachers’ perceptions of provided support or on students’ perceptions of support. The degree to which teachers and students agree is often neither measured nor taken into account. In the current study, we will therefore use a dyadic analysis strategy called the one-with-many design. This design takes into account the nestedness of the data and looks at the importance of reciprocity when examining the influence of teacher support for students’ academic and social functioning. Two samples of teachers and their students from Grade 4 (age 9-10 years) have been recruited in primary schools, located in Turkey and Romania. By using the one-with-many design we can first measure to what degree teachers’ perceptions of support are in line with students’ experiences. Second, this level of consensus is taken into account when examining the influence of teacher support for students’ social well-being and academic functioning.